Leksikon unsur-unsur struktur bangunan rumah adat Joglo Surakarta: Kajian etnolinguistik - Jaya, Mido Mashela; Rajwa, Aliifa Khoiru; Carelino, Alexander Fanky; Mardiyani, Mei Lestari; Nugroho, Miftah (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2025)
The island of Java has many customs and cultures, especially the Joglo traditional house which in some areas have different names and functions. The preservation of cultural heritage is carried out through written documentation using a lexicon to describe the parts of the Joglo traditional house which are important symbols, especially in the lexicon of the Surakarta Joglo traditional house. This research is qualitative and uses a descriptive research type method. The use of observation methods and interview methods are used in this research to collect data. The use of data sources in this study is through secondary and primary type data. The use of data provision techniques through recording and analysis shows that there is a cultural meaning of the elements of the building structure of the Surakarta Joglo traditional house as shown by the data from the object of research which presents both meaning and definition in each structure of the Surakarta Joglo traditional house. The resulting data is categorized into monomorphemic and polymorphemic structures with findings namely roof structure, middle structure, lower structure, and house structure (room).